Use of multi-sensory marketing techniques and its influence on brand experience in retail and HORECA sector - Machala, Agnieszka (2014)
Double degree. A Work Project presented as part of the requirements for the Award of a Masters Degree in Management from the NOVA- School of Business and Economics and Warsaw School of Economics